Optimization of Ultrasound Pretreatment Applications in Biogas Production from Microalgae with the Taguchi Approach - Cinar, Aysenur; Akkaya, Ebru Koca (SPRINGER, 2026)
This study applied ultrasonic pretreatment to improve biogas production from microalgal biomass and to optimize this process using the Taguchi method. In the ultrasonic pretreatment applied to mixed microalgal biomass cultivated in animal wastewater, the variables of power (40-100%), time (75-600s), and solid concentration (0.5-3%) were evaluated. To evaluate the effect of the pretreatment on disruption of the algae cells, the percentage of disintegration was calculated, and biogas production potential of the biomass was measured using biochemical methane potential tests. The calculated signal-to-noise ratio revealed that solid concentration was the significant factor affecting the process, yielding a maximum cell rupture of 34% at the lowest concentration (0.5%). ANOVA analysis of the S/N ratio revealed that the solid concentration was the most significant factor, contributing 53.47% to the microalgal biomass's ultrasonic disintegration, a finding supported by the model's high R-2 value of 0.93. Compared to control samples, the highest biogas production potential increased by 3, 2.75, 2.75, and 1.78 times under the conditions of US-4 (100%, 600s, 0.5%) , US-8 (100%, 300s, 1%), US-10 (60%, 600s, 2%), US-13 (40%, 600s, 3%), respectively. Kinetic modeling based on first order kinetics demonstrated a high correlation (R-2 ranging from 0.85 to 0.99) with the experimental data, confirming that ultrasound pretreatment significantly enhanced the hydrolysis rate constant and accelerated biogas production. Energy efficiency calculations (E-out/E-in) demonstrated an inverse relationship with exposure time. These findings suggest that ultrasound enhances biogas yield, and shorter treatment times are essential to achieve a positive net energy balance.
Keywords: Anaerobic digestion; Disintegration degree; Microalgae; Taguchi method; Ultrasonic pretreatment; ANAEROBIC-DIGESTION; BIOMASS; Energy & Fuels; Environmental Sciences & Ecology